STATUS KEBERLANJUTAN PENGEMBANGAN AGRIBISNIS HORTIKULTURA DI KABUPATEN SUMBA BARAT DAYA, PROVINSI NUSA TENGGARA TIMUR - Ernesta Leha (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Abstract. This research was conducted in the Southwest Sumba regency, East Nusa Tenggara Province. This regency has a great potency of natural resources but with higher poverty level due to the low human resources, limited investments and available technology. The poverty can be solved through the development of sustainable horticulture agribusinesses. The multi-dimensional scaling (MDS) analysis, as a modification of the rapid appraisal of the Status of Farming (RAP-farm) method, was used in this study. The results of the analysis showed that sustainability status of the development of horticulture agribusiness in the Southwest Sumba regency was less sustainable, valued 43.72. This value was obtained according to the assessment of 37 parameters from five dimensions with different sustainability statuses, of which only ecology was quite sustainable (52.12), whereas economy (49.01), social (46.76), technology (43.8), and institutions (48.91) were less sustainable. The sensitive parameters toward the development of sustainable horticulture agribusinesses were (1) land slope and erosion frequency, (2) horticulture products prices and cultivated lands sizes, (3) government service existences and the assistance and extension intensity, (4) soil preparation techniques and compost making, and (5) the existence and conflicts among the farmer groups. Keywords: poverty, horticulture, agribusiness, sustainability, Southwest Sumba.